Islamic Tolerance in Qur'an and Hadith: Implications for Educational Institutions - Alfan Nawaziru Zahara; Umi Sumbulah; Fauzan Zenrif (Khazanah Pendidikan Islam, 2024)
Tolerance is a core value in Islam that is derived from the Qur'an and Hadith, emphasising social harmony and respect for differences. Verses like QS. Al-Baqarah: 256 and QS. Al-Mumtahanah: 8, as well as the hadiths on human relationships, show that diversity is part of the divine will. However, erroneous or limited interpretations can lead to practices that are contrary to these values. Therefore, a contextual approach is important to maintain the relevance of the teachings of tolerance in Islam in the modern era. Islamic educational institutions have a strategic role in instilling the values of tolerance through the curriculum, education, and cultural practices of the school. This study emphasises the importance of reinterpreting religious teachings to answer contemporary socio-cultural challenges, as well as the integration of tolerance values that combine faith, science, and humanity. However, there are significant challenges in interpreting the postulates of tolerance contextually, such as resistance from textualist groups, the dominance of traditionalist perspectives, and ideological pressure. To answer this challenge, a deep interpretive approach from thinkers such as Quraish Shihab and Amin Abdullah is needed for religious texts to make a positive contribution to pluralistic and peaceful societies. This article bridges the gap between textual and contextual studies of tolerance in Islam. By analysing the Qur'an and Hadith, this study enriches the academic discourse on universal values in Islamic teachings and the importance of education as a means of internalising these values. The article also proposes practical strategies, including curriculum reform and teacher training based on Islamic universal values, to build a tolerant and inclusive generation. Empirically based follow-up studies are recommended to evaluate the effectiveness of the implementation of tolerance values in various types of Islamic educational institutions, both madrasas, Islamic boarding schools, and modern Islamic schools.